Quantitative analysis of protein crotonylation identifies its association with immunoglobulin A nephropathy - Lin, Hua (Mol Med Rep, 2020)
Posttranslational modifications (PTMs) to histones such as lysine crotonylation are classified as epigenetic changes. Lysine crotonylation participates in various cellular processes and occurs in active promoters, directly accelerating transcription. The present study performed a proteomics analysis of crotonylation between healthy controls and patients with immunoglobulin A (IgA) nephropathy using tandem mass spectrometry and high-resolution liquid chromatography. The present results identified 353 crotonylated proteins and 770 modification sites, including 155 upregulated and 198 downregulated crotonylated proteins. In total, seven conserved motifs were identified in the present study. The present bioinformatics analysis results suggested a number of the crotonylated proteins exhibited various subcellular localization patterns, such as in the cytoplasm. Protein domains, including thioredoxin, moesin tail and myosin like IQ motif domains were markedly enriched in crotonylated proteins. Kyoto Encyclopedia of Genes and Genomes and functional enrichment analyses suggested significant enrichment of crotonylated proteins in complement and coagulation cascades, and antigen processing and presentation pathways displaying important relationships with IgA nephropathy. The present results suggested that crotonylation occurred in numerous proteins and may play key regulatory roles in IgA nephropathy.